2021
DOI: 10.1038/s41598-020-80547-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fibrinogen in the diagnosis of periprosthetic joint infection

Abstract: Periprosthetic joint infections (PJIs) have become the most catastrophic complication for patients after arthroplasty. Although previous studies have found that many biomarkers have good performance for diagnosing PJI, early diagnosis remains challenging and a gold standard is lacking. This study aimed to investigate the diagnostic accuracy of plasma fibrinogen (FIB) in detecting PJI compared to other traditional biomarks (CRP, WBC and ESR). A total of 156 patients (including 57 PJI and 99 non-PJI patients) wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
1
16
0
Order By: Relevance
“…In knees (septic: 13.5 G/L, aseptic 7.9 G/L) and in hips (septic: 11.6 G/L, aseptic: 7.6 G/L), a higher mean was shown in septic compared with aseptic cases ( p = 0.001 and p = 0.0003, respectively). Yang et al [ 29 ] also reported in a cohort of 156 patients, including 57 PJIs and 99 non-PJIs, a difference between both groups regarding serum WBC (PJI: 7.8 G/L; non-PJI: 6.4 G/L; p < 0.001). In our study [ 2 ], the mean WBC in septic cases ( n = 75) was 8.8 G/L and in aseptic patients ( n = 102), it was 7.0 G/L ( p < 0.0001).…”
Section: White Blood Cell Count (Wbc)mentioning
confidence: 91%
See 4 more Smart Citations
“…In knees (septic: 13.5 G/L, aseptic 7.9 G/L) and in hips (septic: 11.6 G/L, aseptic: 7.6 G/L), a higher mean was shown in septic compared with aseptic cases ( p = 0.001 and p = 0.0003, respectively). Yang et al [ 29 ] also reported in a cohort of 156 patients, including 57 PJIs and 99 non-PJIs, a difference between both groups regarding serum WBC (PJI: 7.8 G/L; non-PJI: 6.4 G/L; p < 0.001). In our study [ 2 ], the mean WBC in septic cases ( n = 75) was 8.8 G/L and in aseptic patients ( n = 102), it was 7.0 G/L ( p < 0.0001).…”
Section: White Blood Cell Count (Wbc)mentioning
confidence: 91%
“…Lower cut-off values were described by Glehr et al [13] (cut-off: 5.48 G/L) and Klim et al [20] (cut-off 5.68), leading to a higher sensitivity (91% and 90%, respectively) but at the expense of specificity (34% and 39%, respectively). Table 3 shows the recent literature of WBC depending on the used infection definition [2,10,11,13,[15][16][17]20,23,25,29,35].…”
Section: White Blood Cell Count (Wbc)mentioning
confidence: 99%
See 3 more Smart Citations